Low back pain research priorities: a survey of primary care practitioners - Das Anurina; Refshauge Kathryn M; Maher Christopher G; Henschke Nicholas; McAuley James H (BMC Family Practice, 2007)
Abstract Background Despite the large amount of time and money which has been devoted to low back pain research, successful management remains an elusive goal and low back pain continues to place a large burden on the primary care setting. One reason for this may be that the priorities for research are often developed by researchers and funding bodies, with little consideration of the needs of primary care practitioners. This study aimed to determine the research priorities of primary care practitioners who manage low back pain on a day-to-day basis. Methods A modified-Delphi survey of primary care practitioners was conducted, consisting of three rounds of questionnaires. In the first round, 70 practitioners who treat low back pain were each asked to provide up to five questions which they would like answered with respect to low back pain in primary care. The results were collated into a second round questionnaire consisting of 39 priorities, which were rated for importance by each practitioner on a likert-scale. The third round consisted of asking the practitioners to rank the top ten priorities in order of importance. Results Response rates for the modified-Delphi remained above 70% throughout the three rounds. The ten highest ranked priorities included the identification of sub-groups of patients that respond optimally to different treatments, evaluation of different exercise approaches in the management of low back pain, self-management of low back pain, and comparison of different treatment approaches by primary care professions treating low back pain. Conclusion Practitioners identified a need for more information on a variety of topics, including diagnosis, the effectiveness of treatments, and identification of patient characteristics which affect treatment and recovery.